Development and testing of a field diagnostic assay for peste des petits ruminants virus - Baron, J.; Fishbourne, E.; Couacy-Hyman, E.; Abubakar, M.; Jones, B.A.; Frost, L.; Herbert, R.; Chibssa, T.R.; Klooster, G. van't; Afzal, M.; Ayebazibwe, C.; Toye, Philip G.; et al. (Hindawi Limited, 2014)
We have developed an immunochromatographic test for the diagnosis of peste des petits ruminants (PPR) under field conditions. The diagnostic assay has been tested in the laboratory and also under field conditions in Ivory Coast, Pakistan, Ethiopia and Uganda. The test is carried out on a superficial swab sample (ocular or nasal) and showed a sensitivity of 84% relative to PCR. The specificity was 95% over all nasal and ocular samples. The test detected as little as 103 TCID50 (50% tissue culture infectious doses) of cell culture-grown virus, and detected virus isolates representing all four known genetic lineages of peste des petits ruminants virus. Virus could be detected in swabs from animals as early as 4 days post-infection, at a time when clinical signs were minimal. Feedback from field trials was uniformly positive, suggesting that this diagnostic tool may be useful for current efforts to control the spread of PPR.